2008
DOI: 10.1111/j.1444-2906.2008.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Sound generated by a payao and comparison with auditory sensitivity of jack mackerelTrachurus japonicus

Abstract: Sound generated by a payao, an anchored bamboo fish aggregating device, is believed to be attractive to fish; but until now, there is no available record of payao‐generated sound. This study presents payao‐generated sound recorded by a hydrophone at water depths of 5, 10 and 15 m from a fixed distance of 3 m relative to the payao, and compares the sound with the auditory sensitivity of jack mackerel Trachurus japonicus measured at discrete frequencies from 100 to 2000 Hz using the auditory brainstem response p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…CRT of YT 0702 was 6 days. These short CRTs were reported before on juveniles (Babaran et al 2008;Mitsunaga et al 2012). These results suggest that the juveniles were on a start line to start to migrate when they reach about 30 cm FL (Aprieto 1991).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CRT of YT 0702 was 6 days. These short CRTs were reported before on juveniles (Babaran et al 2008;Mitsunaga et al 2012). These results suggest that the juveniles were on a start line to start to migrate when they reach about 30 cm FL (Aprieto 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Josse et al (1998) indicated the important role of the SSL, assimilated as food, in vertical and horizontal tuna movements, during daytime and night time. Babaran et al (2008) also suggested the possibility of the coincidence of swimming depth of juveniles and prey around a payao. Mitsunaga et al (2012) reported a diurnal vertical swimming pattern of a juvenile, as if following the diurnal migration patterns of prey organisms in the SSL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a more direct assessment might be needed such as using acoustic techniques to relate the size of schools of fish to these waiting times. The production of sounds by anchored FADs may help orient and attract tuna toward the structure (Babaran et al, 2008), since according to Tolimieri et al (2000), sound can serve as a navigational cue for fishes.…”
Section: Semi-structured Interviewmentioning
confidence: 99%